Development of a Therapeutic Exercise Robot for Wrist and Forearm Rehabilitation - Atlihan, Murat; Akdogan, Erhan; Arslan, M. Selcuk (IEEE, 2014)
In this study, design steps and system concept of a 3 DOF upper limb rehabilitation robot which is called Physiotherabot/WF are introduced. Functional requirements of design, corresponding design parameters and system concept of the robot were examined in detail. Physiotherabot/WF can perform pronation-supination movement for forearm, abduction-adduction and flexion-extension movements for wrist. It can perform passive, active assisted, isotonic, isometric and isokinetic exercises. In order to control the robot, Hybrid Impedance Control (HIC) method is used. The HIC performance is shown by simulation results.
Keywords: rehabilitation robot; biomechatronics design; hybrid impedance control; STROKE; Automation & Control Systems; Computer Science; Engineering; Robotics